Transcriptome Profiling of Immune Cell Types in Peripheral Blood Reveals Common and Specific Pathways Involved in the Pathogenesis of Myositis‐Specific Antibody‐Positive Inflammatory Myopathies. Issue 2 (18th January 2023) - Sugimori, Yusuke; Iwasaki, Yukiko; Takeshima, Yusuke; Okubo, Mai; Kobayashi, Satomi; Hatano, Hiroaki; Yamada, Saeko; Nakano, Masahiro; Yoshida, Ryochi; Ota, Mineto; Tsuchida, Yumi; Nagafuchi, Yasuo; et al.
Abstract : Objective: Idiopathic inflammatory myopathies (IIM) demonstrate characteristic clinical phenotypes depending on the myositis‐specific antibody (MSAs) present. We aimed to identify common or MSA‐specific immunological pathways in different immune cell types from peripheral blood by transcriptome analysis. Methods: We recruited 33 patients with IIM who were separated into the following groups: 15 patients with active disease at onset and 18 with inactive disease under treatment. All patients were positive for MSAs: anti–melanoma differentiation‐associated gene 5 (MDA5) antibody (Ab) in 10 patients, anti‐Mi‐2 Ab in 7, and anti‐aminoacyl‐transfer RNA synthetase (ARS) Ab in 16. The patients were compared with 33 healthy controls. Twenty‐four immune cell types sorted from peripheral blood were analyzed by flow cytometry, RNA sequencing, and differentially expressed gene analysis combined with pathway analysis. Results: The frequencies of memory B cell types were significantly decreased in active patients, and the frequency of plasmablasts was prominently increased in active patients with anti‐MDA5 Ab in comparison with healthy controls. The expression of type I interferon (IFN)‐stimulated genes of all immune cell types was increased in the active, but not inactive, patients. Endoplasmic reticulum stress‐related genes in all IIM memory B cells and oxidative phosphorylation‐related genes in inactive IIM double negative B cells were also increased, suggesting prominent B cell activation in IIM. Furthermore, active patients with anti‐MDA5 Ab, anti‐Mi‐2 Ab, or anti‐ARS Ab were distinguished by IFN‐stimulated and oxidative phosphorylation‐related gene expression in plasmablasts. Conclusion: Unique gene expression patterns in patients with IIM with different disease activity levels and MSA types suggest different pathophysiologies. Especially, B cells may contribute to common and MSA‐specific immunological pathways in IIM.